2019
DOI: 10.1002/maco.201810509
|View full text |Cite
|
Sign up to set email alerts
|

The effect of CeCl3 inhibitor on the localized corrosion of stainless steel in chloride solutions

Abstract: Stainless steels have been used extensively in many sectors such as medical and household appliances as well as construction. This has been primarily due to their high resistance to corrosion attacks, reasonable cost, and excellent mechanical properties. However, when placed in corrosive media stainless steel is susceptible to localized corrosion attacks, especially when placed in chloride solutions. The paper explores the issue of corrosion liability of austenitic (AISI 316) and duplex (UNS S32205) stainless … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…Recently, several environmental and health legislations have limited the use of chromium compounds due to their high toxicity and carcinogenic nature [42,[47][48][49][50], which leads to the urgent search for new and better alternative methods [51][52][53][54][55][56][57][58][59]. For this reason, sulfuric acid anodizing treatment followed by a cerium-molybdenum surface modification process was investigated through this research, to increase the corrosion protection and durability in anodized A390 Al-Si alloy produced under spray-deposited technology.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several environmental and health legislations have limited the use of chromium compounds due to their high toxicity and carcinogenic nature [42,[47][48][49][50], which leads to the urgent search for new and better alternative methods [51][52][53][54][55][56][57][58][59]. For this reason, sulfuric acid anodizing treatment followed by a cerium-molybdenum surface modification process was investigated through this research, to increase the corrosion protection and durability in anodized A390 Al-Si alloy produced under spray-deposited technology.…”
Section: Introductionmentioning
confidence: 99%
“…Petek and Kovačič [ 29 ] have demonstrated that cerium sulfate has a significant inhibitory effect on AISI 420 stainless steel in acidic sulfate solutions. Alar et al [ 30 ] found that cerium chloride in chloride solutions has a good inhibitory effect on austenitic stainless steel (AISI 316) and duplex stainless steel (UNS S32205).…”
Section: Introductionmentioning
confidence: 99%